1997
DOI: 10.1007/s002470050082
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging differentiation of benign and malignant peripheral nerve sheath tumors: use of the target sign

Abstract: The target sign on T2-weighted MR imaging is helpful in differentiating neurofibromas from malignant peripheral nerve sheath tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
128
0
6

Year Published

2001
2001
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(137 citation statements)
references
References 15 publications
3
128
0
6
Order By: Relevance
“…The definition of the target sign has varied in past studies. [8][9][10][11] Koga et al 12 examined these previous articles, defined the characteristic target sign on MRI and clarified its sensitivity and specificity based on histology. In this study, we employed the definitions of a target sign developed by Koga et al: 12 (1) a biphasic pattern on T 2 weighted images (T 2 WIs) and gadolinium (Gd)-enhanced T 1 weighted images (T 1 WIs); (2) higher intensity peripherally and lower intensity centrally on T 2 WIs; and (3) higher intensity centrally by focal enhancement and lower intensity peripherally on Gdenhanced T 1 WIs.…”
Section: Methodsmentioning
confidence: 99%
“…The definition of the target sign has varied in past studies. [8][9][10][11] Koga et al 12 examined these previous articles, defined the characteristic target sign on MRI and clarified its sensitivity and specificity based on histology. In this study, we employed the definitions of a target sign developed by Koga et al: 12 (1) a biphasic pattern on T 2 weighted images (T 2 WIs) and gadolinium (Gd)-enhanced T 1 weighted images (T 1 WIs); (2) higher intensity peripherally and lower intensity centrally on T 2 WIs; and (3) higher intensity centrally by focal enhancement and lower intensity peripherally on Gdenhanced T 1 WIs.…”
Section: Methodsmentioning
confidence: 99%
“…However, it has been shown that these criteria are not reliable indicators of malignancy and can be present in benign neuroˆbromas. 2,5,6 Recently, DWI has been used to detect and characterize tumors. DWI is a technique in which phase-defocusing and -refocusing gradients are used to evaluate the rate of microscopic water diŠu-sion within tissue.…”
Section: Discussionmentioning
confidence: 99%
“…On T2-weighted images, they are either of heterogeneous high signal intensity or display a target sign (68)(69)(70). The target sign is characterized by a hypo-to isointense center surrounded by a peripheral hyperintense ring, which corresponds histologically with a central zone of tightly packed fibers, consisting of collagen or a highly cellular component, and a peripheral zone of nonfibrillary stromal or myxoid material (68)(69)(70)(71). The target pattern is usually absent in large masses and in tumors with cystic, hemorrhagic, or necrotic degeneration (70).…”
Section: Schwannomamentioning
confidence: 99%